HERMES: A Data and Specimens Transporter from the Stratosphere to the Ground—The First Experimental Flight - Giovanni Romeo; Pasquale Adobbato; Simone Bacci; Giuseppe Di Stefano; Alessandro Iarocci; Amedeo Lepore; Massimo Mari; Silvia Masi; Francesco Pongetti; Giuseppe Spinelli; Massimiliano Vallocchia (Drones, 2023)
Large stratospheric balloons are the easiest access to near space. Large long duration balloons (LDBs) can float in the stratosphere for weeks collecting measurements (e.g., astrophysical or geophysical data) or samples (e.g., contaminants, volcanic ash, micrometeorites). The recovery of data media and samples is a common problem in this type of experiment because direct radio communication becomes useless when the balloon crosses the horizon, and satellite links are too slow and expensive. For this reason, physical recovery of the payload is mandatory to obtain experimental results, which is a difficult task, especially in polar regions. The goal of HERMES (HEmera Returning MESsenger) is to allow researchers to obtain experimental data prior to payload recovery. HERMES is a system equipped with an autonomous glider capable of physically transporting data and samples from the stratosphere to a recovery point on the ground. The glider is installed on the balloon payload via a remotely controlled release system and is connected to the main computer to store a copy of the scientific data and to receive the geographic coordinates of the recovery point. This allows scientists to obtain experimental results before recovering the payload. The article describes HERMES and the first experimental flight of the entire system, which was conducted at Esrange Space Center (Kiruna, Sweden) in July 2022.